Hydroxyl radical induced chemiluminescence of hyperbranched polyethyleneimine protected silver nanoclusters and its application in tea polyphenols detection. Issue 21 (17th May 2017) - Zhao, Shuang; Chen, Chen; Li, Zenghe; Yuan, Zhiqin; Lu, Chao
Abstract : Selective tea polyphenols detection based on hydroxyl radical induced chemiluminescence of hyperbranched polyethyleneimine protected silver nanoclusters is presented. Abstract : In this report, a simple approach for generating chemiluminescence (CL) of hyperbranched polyethyleneimine protected silver nanoclusters (hPEI-AgNCs) in solution by hydroxyl radicals (˙OH) is proposed. Emission of this CL system originates from excited AgNCs rather than from reaction intermediates, which is different from other metal nanoclusters involving CL reactions. Notably, in the presence of tea polyphenols (TPPs), the ˙OH induced CL signal is restrained, which is due to the TPPs-induced reduction of ˙OH. Therefore, a facile CL approach for TPPs sensing based on the inhibition effect of TPPs towards the ˙OH has been developed. This simple CL detection method exhibits a linear response toward TPPs in the concentration range from 2.52 to 76.2 μM with a limit of detection of 2.52 μM. In addition, the proposed method displays high selectivity toward TPPs over other small molecules or metal ions, includingl -theanine, l -alainine, l -asparagine, paraxanthine, glycine, glucose, Na +, K +, Mg 2+, Zn 2+ and Fe 3+ . Compared with reported colorimetric or fluorimetric approaches, this new system shows comparable or better selectivity. The proposed method can be readily used for TPPs content evaluation from tea sample infusions.